A framework for the generation and management of self-adaptive enterprise applications (2015)
Demand for self-adaptive enterprise applications has been on the rise over the last years. Such applications are expected to satisfy context-dependent quality requirements in varying execution conditions. Their dynamic nature constitutes challenges with respect to their architectural design and development, and the guarantee of the agreed quality scenarios at runtime. In this paper we present the constituting elements of Shift, a framework that integrates (i) facilities and mechanisms for managing self-adaptive enterprise applications, (ii) automated derivation of self-adaptive enterprise applications and their respective monitoring infrastructure, and (iii) decision support for the assisted recomposition of self-adaptive applications.